2011
DOI: 10.1007/s10664-011-9159-7
|View full text |Cite
|
Sign up to set email alerts
|

Using structural and textual information to capture feature coupling in object-oriented software

Abstract: Previous studies have demonstrated the relationship between coupling and external software quality attributes, such as fault-proneness, and the application of coupling to software maintenance tasks, such as impact analysis. These previous studies concentrate on class coupling. However, there is a growing focus on the study of features in software, and features are often implemented across multiple classes, meaning class-level coupling measures are not applicable. We ask the pertinent question, "Is measuring co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 92 publications
1
36
0
4
Order By: Relevance
“…That is, a file is typically much "bigger" than a method. Previous works on the application of information retrieval techniques in software engineering have observed a similar sensitivity trend with respect to the size of the document and the accuracy of the intended tasks (Revelle et al 2011). For the evolutionary couplings, only the co-change information in commits was utilized for evolutionary couplings.…”
Section: Rq2: Does the Choice Of Granularity (Ie File Vs Method) mentioning
confidence: 73%
“…That is, a file is typically much "bigger" than a method. Previous works on the application of information retrieval techniques in software engineering have observed a similar sensitivity trend with respect to the size of the document and the accuracy of the intended tasks (Revelle et al 2011). For the evolutionary couplings, only the co-change information in commits was utilized for evolutionary couplings.…”
Section: Rq2: Does the Choice Of Granularity (Ie File Vs Method) mentioning
confidence: 73%
“…Kuhn et al (2007) proposed the use of IR techniques to exploit linguistic information found in source code, such as identifiers (i.e., class or method) names and comments. Revelle et al (2011) define new feature coupling metrics based on structural and textual source code information. Kagdi et al (2013) in their study on integrating conceptual and logical coupling metrics for change impact analysis suggest that measurement of conceptual metrics is better employed at the class level than at the method level.…”
Section: Related Workmentioning
confidence: 99%
“…There are also other sources like the software documentation, web search engines, source code examples or programming tutorials. Developers can seek for source code to find files or code locations for further modifications [34] or look for a code description to better understand the part of the code they need to edit based on a similar situation or a problem.…”
Section: Task Relevant Information Sourcesmentioning
confidence: 99%
“…Revelle et al [34] inspected a set of coupling metrics on the structural and the semantic level where the developers answered that feature couplings on a higher level of abstraction than classes are useful. Bavota et al [4] explored the developers' perceptions of software couplings.…”
Section: Related Workmentioning
confidence: 99%